Ultrahigh Sensitivity of a Plasmonic Pressure Sensor with a Compact Size - Chung-Ting Chou Chao (MDPI AG, 2021)
This study proposes a compact plasmonic metal-insulator-metal pressure sensor comprising a bus waveguide and a resonator, including one horizontal slot and several stubs. We calculate the transmittance spectrum and the electromagnetic field distribution using the finite element method. When the resonator’s top layer undergoes pressure, the resonance wavelength redshifts with increasing deformation, and their relation is nearly linear. The designed pressure sensor possesses the merits of ultrahigh sensitivity, multiple modes, and a simple structure. The maximum sensitivity and resonance wavelength shift can achieve 592.44 nm/MPa and 364 nm, respectively, which are the highest values to our knowledge. The obtained sensitivity shows 23.32 times compared to the highest one reported in the literature. The modeled design paves a promising path for applications in the nanophotonic field.